Metalotioneínas en bivalvos marinos - Lemus, Mairin (2016)
Metallothioneins (MTs) are very particular proteins with a molar mass between 6-7 kDa, rich in cysteine (30%) and absence of aromatic amino acids. They undertake the maintenance of homeostasis of Cu and Zn and the detoxification of non-bioessential metals as Cd and Hg, and they are scavengers of free radicals, mainly of free hydroxyl and superoxides. These proteins are involved in a large number of physiological processes that have been studied in detail in vertebrate organisms. However, in invertebrates the study has not advanced at the same rate. Studies of MTs in bivalve mollusks have increased as a physiological response to heavy metal exposure. These invertebrates have been used widely as biomarkers of heavy metals, which supported their use as a tool to determine contaminated environments. More recently, isoforms of the MTs on at different stages of the life cycle. Additionally environmental and xenobiotic factors modulate the expression and function of these proteins. The studies have demonstrated that there is a great polymorphism of MTs in bivalves, Some MTs can be induced by heavy metals, other are only associated with physiological processes. This revision deals about the characteristics and function of MTs, starting from the wide available knowledge in vertebrates and less knowledge in invertebrates.